Pengaruh Stimulasi Sensori dengan Metode Terapi Kelompok terhadap Skor Geriatric Depression Scale Pada Lansia di Komunitas - Puspitosari, Aniek; Nurhidayah, Ninik (Jurnal Kesehatan Komunitas, 2025)
People experience a natural aging process that causes changes in physical, biological and psychological conditions. These changes can lead to depression. Sensory stimulation in group therapy is used to provide sensory stimulation to the senses in order to express what is felt so it can help in reducing the symptoms of depression. This study aims to determine the effect of sensory stimulation group therapy on the level of depression seen from the Geriatric Depression Scale (GDS) score. The study was a one group pretest-posttest design with a sample size of 40. The research instrument used the GDS-30. Sensory stimulation group therapy was given 8 times. The characteristics of the research results were dominated by female samples, middle adulthood age category, non-working category and marital status still having a partner. Wilcoxon test p = 0.000 means p-value < a (0.05) indicates that sensory stimulation group therapy affects the GDS score. Sensory stimulation group therapy has an effect on reducing GDS scores because some of the activities provided are able to maintain individual sensory function and the implementation of group therapy has a positive effect on social life.